English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

log base-2 [ log base-3(log base-2 of x)] = 1, then x?
Options are 1)128 2)512 3)12 4)0

No need of any explanations. Just tell me the answer. One lucky person will get 10 points.

2007-03-20 04:33:36 · 5 answers · asked by Kapil 3 in Science & Mathematics Mathematics

5 answers

log2(log3(log2(x))) = 1

2^[log2(log3(log2(x)))] = 2^1

log3(log2(x)) = 2

3^[log3(log2(x))] = 3^2

log2(x) = 9

2^[log2(x)] = 2^9

x = 512


I know you said explanation wasn't necessary, but its easier to check imo.

2007-03-20 04:40:04 · answer #1 · answered by Bhajun Singh 4 · 0 0

log base-2 [ log base-3(log base-2 of x)] = 1
=> log base-3(log base-2 of x) = 2^1=2
=> log base-2 of x = 2^3 = 8
=> x = 2^8 = 512

2007-03-20 11:50:40 · answer #2 · answered by a_ebnlhaitham 6 · 1 0

2)512

2007-03-20 11:52:36 · answer #3 · answered by Vinay C 1 · 1 0

My answer doesn't match any of your options, I'm not sure but it is -1.080059739.
I'm sorry, I thought the base is negative, considering the base is positive, my answer is 512.

2007-03-20 12:04:12 · answer #4 · answered by Jan Francis M 2 · 1 0

log(b2) = log base 2, log(b3) = log base 3
log(b2) [ log(b3) (logb2 (x) ] = 1
2^(1) = log(b3).[ logb2 (x) ]
3² = logb2 (x)
9 = logb2 (x)
x = 2^(9) = 512
ANSWER 2

2007-03-20 15:16:49 · answer #5 · answered by Como 7 · 1 0

fedest.com, questions and answers